2021
DOI: 10.1111/1750-3841.16004
|View full text |Cite
|
Sign up to set email alerts
|

Nondestructive detection of total soluble solids in grapes using VMD‐RC and hyperspectral imaging

Abstract: Total soluble solids (TSS) are one of the most essential attributes determining the quality and price of fruit. This study aimed to use hyperspectral imaging (HSI) and wavelength selection for nondestructive detection of TSS in grape. A novel method involving variational mode decomposition and regression coefficients (VMD‐RC) was proposed to select feature wavelengths. VMD was introduced to decompose the hyperspectral images data of samples with bands of (400.68–1001.61 nm) to get a series of feature component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Total soluble solid (TSS) is among the most essential attributes that determine the quality of fruits. TSS is dominated by total sugar content, with a minor contribution from soluble proteins, amino acids, and other organic materials (Xu et al, 2022). In this study, the TSS of 'Summer Black' and 'Flame Seedless' was found to be 25.12 and 24.71°Brix, respectively, which was higher than other grape varieties, while 'Victoria' had the lowest TSS of 14.93°Brix.…”
Section: Basic Berry Quality Indexes Of Different Grape Varieties At ...mentioning
confidence: 53%
“…Total soluble solid (TSS) is among the most essential attributes that determine the quality of fruits. TSS is dominated by total sugar content, with a minor contribution from soluble proteins, amino acids, and other organic materials (Xu et al, 2022). In this study, the TSS of 'Summer Black' and 'Flame Seedless' was found to be 25.12 and 24.71°Brix, respectively, which was higher than other grape varieties, while 'Victoria' had the lowest TSS of 14.93°Brix.…”
Section: Basic Berry Quality Indexes Of Different Grape Varieties At ...mentioning
confidence: 53%
“…In the case of the TSS, which is the classical and most well-known grape maturity parameter, values of R P 2 = 0.91 and SEP = 1.03 were obtained, with RPD well above 3.0 (8.19, Table ), clearly demonstrating the possibility of accurately estimating this variable using noninvasive HSI. TSS has been studied by HSI in red grapes. ,, Good results were obtained in all of them, with good correlations and RPD between 1 and 4. On the other hand, there is a study in which HSI is used to estimate the TSS in red grapes and white grapes.…”
Section: Resultsmentioning
confidence: 98%
“…Currently, HSI technology has been widely used in the quality and safety detection of agricultural products ( Li et al., 2018 ; Yao et al., 2022 ). Some researchers measured the content of soluble solids in fruits by hyperspectral imaging technology ( Li et al., 2016a ; Gao et al., 2022 ; Xu et al., 2022b ). Furthermore, some researchers detected aflatoxin in corn, almond, and other crops by HSI technology ( Chu et al., 2017 ; Kimuli et al., 2018 ; Mishra et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%